Resposta de capim pé-de-galinha (Eleusine spp.) ao herbicida glyphosate - Ulguim, André da Rosa (2012)
The goosegrass (Eleusine spp.) is an annual plant, found in agricultural crops in Rio Grande do Sul (RS), where has been control failures in response to glyphosate application, suggesting the resistance of the species to this herbicide. The objectives of this research were to identify the occurrence of resistance of goosegrass to glyphosate in RS, determine the LD50 and GR50, identify the mechanism of resistance, evaluate the factors involved in the observed control failures, and propose alternatives to chemical control to these biotypes. Thus, plant seeds of failures herbicide control, suspected of resistance, were collected in eight cyties soybean producers in RS, and used in the experiments. The results showed that all the plants from seeds collected has been controlled by glyphosate when applied at a rate of 2160 g a.e. ha-1. The biotype 12.3, from Boa Vista do Incra, show a low level resistance to glyphosate, with resistance factor (RF) of 1.17, according to LD50, and the mechanism that confers resistance is not due to the metabolism of glyphosate by cyt-P450 complex, or herbicide absorption. The suspected resistant biotypes have lower control when glyphosate is sprayed in advanced stages of growth, as one or two tillers, that may be the cause of control failures observed in crop area. The ACCase inhibiting herbicides (clethodim and fluazifop-p-butyl) and amonium-glufosinate efficiently control these biotypes, at four leaves to a one tiller stage, being an alternative to chemical control of this weed.